2016
DOI: 10.1016/j.jpeds.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal Betamethasone: A Prolonged Time Interval from Administration to Delivery Is Associated with an Increased Incidence of Severe Intraventricular Hemorrhage in Infants Born before 28 Weeks Gestation

Abstract: Objective To examine the effects of antenatal steroids on severe intraventricular hemorrhage (IVH) in infants born during the IVH vulnerable period (<28 weeks gestational age) and to evaluate rates of IVH correlated with the time interval between treatment or retreatment and birth. Study design 429 infants (< 28 weeks gestation), who delivered ≥24 hours after the first BMZ course (two doses), were divided into groups based on the interval between the first course of BMZ and delivery: <10 days or ≥10 days. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 48 publications
0
17
0
4
Order By: Relevance
“…Two major IVH risk factors, hypotension requiring inotropic support 12 14 and patent ductus arteriosus 15 , 16 , are equally important in the development of CH. Likewise, antenatal steroids, which have a well-described association with a reduction in IVH rates 17 , 18 , do not exert a disease-specific effect in this analysis.…”
Section: Discussionmentioning
confidence: 56%
“…Two major IVH risk factors, hypotension requiring inotropic support 12 14 and patent ductus arteriosus 15 , 16 , are equally important in the development of CH. Likewise, antenatal steroids, which have a well-described association with a reduction in IVH rates 17 , 18 , do not exert a disease-specific effect in this analysis.…”
Section: Discussionmentioning
confidence: 56%
“…Unless delivery was felt to be imminent, all mothers delivering before 34 weeks gestation were given antenatal BMZ (two 12-mg doses administered 24 hours apart). Prior in vitro (14) and in vivo (1517) studies have shown that antenatal corticosteroids can improve lung function and decrease the risk of severe IVH as early as 7 hours after dosing, however, these effects are reversible and begin to wane by 9 days after the first dose (14,17). Therefore, the infants in our study were divided into two groups depending on the interval between the first dose of antenatal BMZ and delivery: Group A (“inadequate BMZ treatment”) included infants who were either never treated, delivered before 7 hours, or delivered more than 9 days after the first dose of BMZ.…”
Section: Human Patient Population and Pda Treatment Protocolmentioning
confidence: 99%
“…The WHO reanalysis 2 of the Roberts meta-analysis found that for each benefit, 6 the effective interval from treatment to delivery differed (e.g. deaths decreased for intervals <48 h only) while respiratory distress syndrom (RDS) decreased from 48 h to 7 days but not after 7 days and IVH decreased only for an interval >48 h. Liebowitz and Clyman 39 reported increased IVH for an interval from treatment of >10 days and Ring et al 40 reported an increase risk of ventilator support for fetuses exposed to ACS at <28 weeks who delivered at >28 weeks. The long intervals after ACS have not been considered as an important variable in response and are difficult to study in clinical cohorts unless there are time-matched control groups, 19 but this question can be studied with some precision in large animal models.…”
Section: Beta P Infusions To Test Minimum Exposure and Durability Ofmentioning
confidence: 99%